AMBIVALENSI SIKAP BUDAYA PADA MASYARAKAT DI NEGARA BERKEMBANG: DALAM KONTEKS PENERAPAN 'RAGAMHIAS' TRADISI BUDAYA JAWA PADA ARSITEKTUR MODERN - Djoko Sutjipto (Universitas Trisakti, 2006)
AbstractAmbivalency of cultural attitude is an universal symptom, that occured in several nations of development countries, whose faced with difficult choise of two pardgigms. Either keep loyal to the old norms (traditional), or takeover a new ones (modern). This phenomenon usually done in transition period, characterized with changeover of values. A wisdom thoise it's best not